2021
DOI: 10.1519/jsc.0000000000003456
|View full text |Cite
|
Sign up to set email alerts
|

Strength-Power Tests are More Effective When Performed After Exhaustive Exercise in Discrimination Between Top-Elite and Elite Wrestlers

Abstract: Özbay, S and Ulupinar, S. Strength-power tests are more effective when performed after exhaustive exercise in discrimination between top-elite and elite wrestlers. J Strength Cond Res 36(2): 448-454, 2022-This study aimed (a) to analyze strength-power variables in top-elite and elite wrestlers, (b) to identify which variables allow for discrimination between them, and (c) to investigate whether the results changed when the tests were performed after exhaustive exercise. Twenty-six male wrestlers who won medal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…In a different study that used similar tests with adolescent handball players, the discriminant analysis predicted successful and less successful players with an overall accuracy of 73.6% (Palamas et al, 2015). Additionally, Özbay and Ulupınar (2020) found that laboratory tests performed with classical methods can accurately distinguish elite athletes from others with an overall accuracy of 65.4%. Another study showed that there is a 0.68 correlation (r 2 = 0.46) between musculoskeletal fitness and body composition and emphasized the importance of this finding (Nikolaidis, 2014).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a different study that used similar tests with adolescent handball players, the discriminant analysis predicted successful and less successful players with an overall accuracy of 73.6% (Palamas et al, 2015). Additionally, Özbay and Ulupınar (2020) found that laboratory tests performed with classical methods can accurately distinguish elite athletes from others with an overall accuracy of 65.4%. Another study showed that there is a 0.68 correlation (r 2 = 0.46) between musculoskeletal fitness and body composition and emphasized the importance of this finding (Nikolaidis, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…The handgrip strength and standing broad jump tests have been used in scientific studies for more than 50 years as valid and reliable methods for measuring musculoskeletal fitness (Everett & Sills, 1952;Ince & Ulupinar, 2020;Kane & Meredith, 1952;Wind et al, 2010). These tests have also been used to determine isometric strength, or muscle strength, in many different sections of the population (including amateur-professional, male-female, children, youth and adults) to identify their strength-power profile (Fukuda et al, 2013;Özbay & Ulupınar, 2020;Peterson, Alvar, & Rhea, 2006;Wind et al, 2010). Similarly, according to previous studies, the 4 × 10-m shuttle run test is a reliable test for measuring motor fitness (Calatayud et al, 2017;Ortega et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…33 Furthermore, greater improvements in upper body strength endurance tests have been observed in more skilled wrestlers. 34 Modern day RL training incorporates frequent grappling and wrestling training. However, potential relationships between either maximal or strength endurance and other forms of TA in RL players have not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The structural coefficient was used to determine the variables that discriminate between elite and sub-elite. A structural coefficient above .30 was considered as relevant for the interpretation of the linear vectors (Özbay & Ulupınar, 2020).…”
Section: Frequency Speed Of Kick Testmentioning
confidence: 99%
“…Vertical jump tests have been used in sports requiring explosive strength for diverse goals, including evaluating the lower limb neuromuscular power (Liebermann & Katz, 2003), identifying Silva, Del Vecchio, Picanço, Takito, & Franchini, 2011). Combat sports athletes, therefore, are expected to have high levels of anaerobic capacity for all-out attacks during the fight, also need a high aerobic energy system to replenish high-energy phosphates to maintain the anaerobic power-requiring attacks (Özbay & Ulupınar, 2020;Podrigalo, Volodchenko, Rovnaya, & Stankiewicz, 2017). With various methods such as proper and planned training and regular nutrition, kickboxers are trying to increase their competition performance (Franchini, Cormack, & Takito, 2019;Reale, Slater, & Burke, 2017).…”
Section: Introductionmentioning
confidence: 99%